PELAKSANAAN KEGIATAN PEMBELAJARAN BERNYANYI LAGU DAERAH SEBAGAI UPAYA MEMBENTUK RASA PERCAYA DIRI SISWA KELAS VIII SMP NEGERI 7 GORONTALO - Ladiku, Fahril; Ohi, Rahmawati; Karlan, La Ode; Pulukadang, Mimy Astuty; Semiaji, Trubus (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to describe the implementation of learning activities in singing regional songs as an effort to build the self-confidence of eighth-grade students at SMP Negeri 7 Gorontalo. The background of this research is based on the importance of developing students’ self-confidence through the arts, particularly in music education. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The research subjects are the Cultural Arts teacher and the eighth-grade students involved in the regional song singing activities. The results of the study show that the implementation of singing regional songs was systematically designed through stages of song introduction, vocal practice, and classroom performance. These activities were able to increase students’ courage in self-expression, reduce shyness, and encourage active participation in learning. The conclusion of this research is that learning regional songs has a positive contribution to building and enhancing students’ self-confidence. Therefore, it is recommended that similar activities continue to be developed and become an integral part of cultural arts learning in schools.